2022
DOI: 10.1038/s41467-022-28402-9
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome of the buffalo digestive tract

Abstract: Buffalo is an important livestock species. Here, we present a comprehensive metagenomic survey of the microbial communities along the buffalo digestive tract. We analysed 695 samples covering eight different sites in three compartments (four-chambered stomach, intestine, and rectum). We mapped ~85% of the raw sequence reads to 4,960 strain-level metagenome-assembled genomes (MAGs) and 3,255 species-level MAGs, 90% of which appear to correspond to new species. In addition, we annotated over 5.8 million nonredun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 108 publications
(135 reference statements)
6
50
0
Order By: Relevance
“…In addition, Malakar et al [ 20 ] compared fiber degradation in vitro by inoculum with cow’s and buffalo’s ruminal bacteria and fungi and reported that fiber degradation in buffalo was significantly higher than in dairy cows. A recent metagenomic study also reported that buffalo rumen microbiota has stronger fiber degradation and less methane production potential than dairy cow rumen microbiota [ 21 ]. Therefore, it is suggested that the dairy buffaloes may have different compositions and functions in rumen microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Malakar et al [ 20 ] compared fiber degradation in vitro by inoculum with cow’s and buffalo’s ruminal bacteria and fungi and reported that fiber degradation in buffalo was significantly higher than in dairy cows. A recent metagenomic study also reported that buffalo rumen microbiota has stronger fiber degradation and less methane production potential than dairy cow rumen microbiota [ 21 ]. Therefore, it is suggested that the dairy buffaloes may have different compositions and functions in rumen microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, limited study has focused on identifying and understanding the establishment pattern and function of ruminal microbes in dairy buffaloes using high-throughput sequencing technology. Only a few studies have reported that analyzed the rumen microbiome of buffaloes using metagenomic approaches or 16S rRNA gene amplicon sequencing [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, age-related rumen microbial functions have been rarely studied in buffaloes using a metagenomic approach.…”
Section: Introductionmentioning
confidence: 99%
“…And MetaSNV (v 1.0.3) 23 was used to calculate the average coverage for each MAGs in BAM files. As the cut-off of MAG’s presence/absence, average coverage was adjusted using data size of each sample, and copresent MAGs were defined as the MAGs presented (average coverage > 1) 20 in every sample of cow, goat, co-inoculum group, and initial inocula. The rest of MAGs couldn’t meet the threshold in all samples were defined as non-copresent MAGs.…”
Section: Methodsmentioning
confidence: 99%
“…Estimated genome size of MAG was corrected as described in previous study using completeness and contamination 16 . In addition, the obtained MAGs were compared to the rumen MAGs set collected from previous studies (n = 22506) 9,[17][18][19][20] and the GTDB representative genomes (n = 31910) using fastANI (v 1.1) 21 .…”
Section: De Novo Metagenome Assembly Binning and Genome Annotationmentioning
confidence: 99%
See 1 more Smart Citation